Are Smaller Nanoparticles Always Better? Understanding the Biological Effect of Size-Dependent Silver Nanoparticle Aggregation Under Biorelevant Conditions - Bélteky, Péter (Int J Nanomedicine, 2021)
PURPOSE: Silver nanoparticles (AgNPs) are one of the most commonly investigated nanomaterials, especially due to their biomedical applications. However, their excellent cytotoxic and antimicrobial activity is often compromised in biological media due to nanoparticle aggregation. In this work, the aggregation behavior and the related biological activity of three different samples of citrate capped silver nanoparticles, with mean diameters of 10, 20, and 50 nm, respectively, were examined. METHODS: Following nanoparticle synthesis and characterization with transmission electron microscopy, their aggregation behavior under various pH values, NaCl, glucose, and glutamine concentrations, furthermore in cell culture medium components such as Dulbecco’s Modified Eagle’s Medium and fetal bovine serum, was assessed through dynamic light scattering and ultraviolet-visible spectroscopy. RESULTS: The results indicated that acidic pH and physiological electrolyte content universally induce micron-scale aggregation, which can be mediated by biomolecular corona formation. Remarkably, larger particles demonstrated higher resistance against external influences than smaller counterparts. In vitro cytotoxicity and antimicrobial assays were performed by treating cells with nanoparticulate aggregates in differing stages of aggregation. CONCLUSION: Our results revealed a profound association between colloidal stability and toxicity of AgNPs, as extreme aggregation led to the complete loss of biological activity. The higher degree of aggregation resistance observed for larger particles had a significant impact on the in vitro toxicity, since such samples retained more of their activity against microbes and mammalian cells. These findings lead to the conclusion that aiming for the smallest possible nanoparticles might not be the best course of action, despite the general standpoint of the relevant literature.